East African Community regional customs and tax code of ethics and conduct - EAC (EAC, 2019)
The EAC Code of Ethics and Conduct sets the requirements of conduct for Customs and Tax Officials within the Community in the course of carrying out their functions and the action plan spells out what and how the integrity program will be undertaken. The overall purpose of the Code of Ethics and Conduct is to guide the behavior and conduct of EAC Customs and Tax Officials and foster integrity. It also a tool for guiding the customs administrators on how to deal with integrity issues of the staff.
Pages 24. Colored
Keywords: Customs Union; Common Market